A comparative evaluation of the sustainability of alternative aeration strategies in biological wastewater treatment to support net-zero future. (10th November 2022) - Pryce, David; Kapelan, Zoran; Memon, Fayyaz A.
Abstract: In the plight for sustainable development and to support net zero ambitions for climate change mitigation, a broad range of aeration strategies have been developed with the hope of improving efficiency to minimize environmental and economic costs associated with the wastewater treatment processes. However, a balance is levied between reducing oxygen availability and hindering aerobic processes thus compromising performance. In the present work, we evaluate and compare the sustainability of a range of investigated strategies including continuous aeration (CA) at different dissolved oxygen (DO) setpoints (0.5 mg/L, 2.5 mg/L, 4.5 mg/L) and intermittent aeration (IA) at different oxic-anoxic portions (2.5 h on/0.5 h off, 2.0 h on/1.0 h off, 1.5 h on/1.0 h off). To achieve this, an eco-efficiency assessment is performed based on the results of previous life cycle impact and costing analyses for each strategy, while also incorporating a third factor to account for their respective treatment performance. The results demonstrate a clear pattern of increased sustainability for the IA strategies (0.54–0.56 Pt/m 3 ), compared to the CA strategies (0.76–0.77 Pt/m 3 ). While only negligible difference was observed within each aeration type, the trade-off between environmental and economic efficiency and treatment performance was distinct in CA strategies. At the individual pollutant level, IA strategies demonstrated decreasing sustainability for total phosphorous (TP) removal as the anoxic cycle portion increased, while CA at 0.5 mg/L was shown to be the most sustainable strategy for the removal of this pollutant (0.61 Pt/m 3 ). Further work is suggested to incorporate the relative N2 O emissions generated by each strategy and to investigate other strategies based on automated control. Graphical abstract: Image 1 Highlights: The sustainability of 6 aeration strategies in wastewater treatment is evaluated. Intermittent aeration is more sustainable than continuous. Increasing performance compromises eco-efficiency in continuous aeration strategies.